2009
DOI: 10.1089/ast.2008.0283
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Mixotrophic Protists and Catastrophic Darkness

Abstract: Catastrophically darkened photic zone conditions in water bodies are postulated to be induced by a diversity of mechanisms that are recorded in the geological record, including asteroid and comet impacts and large-scale volcanic eruptions. Giant wildfires, such as those that followed the great fires in Siberia in 1915, have been directly shown to cause large reductions in sunlight penetrating to the ground. Previous studies on the response of phototrophs to sudden prolonged darkness have focused on the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Photosynthetic flagellates utilizing phagotrophy for longterm dark survival was previously suggested [24,25]. As noted above, this is consistent with observations of G. cryophila and other Antarctic cryptophytes that engage in autotrophic energy production, but may not require photosynthesis for survival.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Photosynthetic flagellates utilizing phagotrophy for longterm dark survival was previously suggested [24,25]. As noted above, this is consistent with observations of G. cryophila and other Antarctic cryptophytes that engage in autotrophic energy production, but may not require photosynthesis for survival.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, micronutrient deficiencies, particularly iron, have been hypothesized as factors controlling phytoplankton growth in the Southern Ocean and could be a major resource targeted by the phagotrophic activity of mixotrophic flagellates [22,23]. Mixotrophy has even been proposed as a strategy that phytoflagellates could use to survive the austral winter to enter spring as actively growing populations [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Reboud and Bell (1997) showed that experimental populations of Chlamydomonas subjected to an environment fluctuating between light and dark conditions every few generations tended to evolve into generalists capable of growing well in both. Jones et al (2009) have speculated that mixotrophic protists could survive the "catastrophic darkening" associated with volcanic eruptions and asteroid impacts and be responsible for the rapid resumption of primary production after the event.…”
Section: Alternotrophymentioning
confidence: 99%
“…Although mixotrophy might have been a survival advantage to some species17, it cannot solely explain the differential extinction. Phagotrophic mixotrophy is unknown in diatoms and some mixotrophic dinoflagellates have been reported to encyst when exposed to sudden darkness18.…”
mentioning
confidence: 99%